BAIT PREFERENCE AND BUTTERFLY DIVERSITY (LEPIDOPTERA: PAPILIONOIDEA) CAUGHT BY BAIT TRAP IN LANGSA URBAN FOREST, LANGSA, ACEH, INDONESIA - Sari, Herlina Putri Endah; Putri, Kartika Aprilia; Persada, Andri Yusman; Peggie, Djunijanti; Wafa, Imti Yazil (Treubia, 2026)
Butterflies are important for the ecosystem and human life. The presence of butterflies has also become an attraction for nature-based tourism. Langsa Urban Forest (LUF) is an ecotourism site in Langsa City with various biodiversity, including butterflies. For now, data on butterfly diversity in LUF is limited to the active collection using insect nets. This research aimed to complete the database of butterflies in LUF by passive collection to support conservation in LUF. Data was collected for 3 months in the early rainy season (from late August to October 2023), with 8 repetitions using the bait trap method. Results showed 13 species from 3 families with 37 individuals. There were 7 species newly recorded, making a total of 43 species in LUF. From 2 different traps used, 9 species preferred banana bait, 6 species preferred shrimp paste bait, and 2 species trapped in both baits. From 13 species collected by bait trap, 11 species are categorized as Not Evaluated and 2 species are Least Concern by the IUCN Red List.